2021
DOI: 10.1038/s41563-021-01070-8
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer electronic coupling on demand in a 2D magnetic semiconductor

Abstract: When monolayers of two-dimensional (2D) materials are stacked into van der Waals structures, interlayer electronic coupling can introduce entirely new properties, as exemplified by recent discoveries of moiré bands that host highly correlated electronic states and quantum dot-like interlayer exciton lattices. Here we show the magnetic control of interlayer electronic coupling, as manifested in tunable excitonic transitions, in an A-type

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
257
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(284 citation statements)
references
References 39 publications
(42 reference statements)
26
257
0
1
Order By: Relevance
“…Scanning tunneling spectroscopy measurements have shown that the Fermi level is very close to the bottom of -or possibly inside-the conduction band and that charge carriers are electrons [23], but their microscopic origin (i.e., what is the doping mechanism) and precise density are currently unknown. Rather uncommonly, the relatively large low-temperature conductivity -which confirms the presence of sizable non-intentional doping-coexists with a bright fluorescence observed in photoluminescence experiments (see Figure 1e) [24]. Additionally, the same band structure calculations (see Figure 1b) predicting a large bandwidth also show an extremely pronounced anisotropy: the bandwidth is about 1.5 eV in the Γ − Y (which corresponds to the crystallographic b-axis), but nearly vanishes in the perpendicular Γ − X direction (i.e., in the a-direction) [24,25].…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Scanning tunneling spectroscopy measurements have shown that the Fermi level is very close to the bottom of -or possibly inside-the conduction band and that charge carriers are electrons [23], but their microscopic origin (i.e., what is the doping mechanism) and precise density are currently unknown. Rather uncommonly, the relatively large low-temperature conductivity -which confirms the presence of sizable non-intentional doping-coexists with a bright fluorescence observed in photoluminescence experiments (see Figure 1e) [24]. Additionally, the same band structure calculations (see Figure 1b) predicting a large bandwidth also show an extremely pronounced anisotropy: the bandwidth is about 1.5 eV in the Γ − Y (which corresponds to the crystallographic b-axis), but nearly vanishes in the perpendicular Γ − X direction (i.e., in the a-direction) [24,25].…”
Section: Introductionmentioning
confidence: 53%
“…Rather uncommonly, the relatively large low-temperature conductivity -which confirms the presence of sizable non-intentional doping-coexists with a bright fluorescence observed in photoluminescence experiments (see Figure 1e) [24]. Additionally, the same band structure calculations (see Figure 1b) predicting a large bandwidth also show an extremely pronounced anisotropy: the bandwidth is about 1.5 eV in the Γ − Y (which corresponds to the crystallographic b-axis), but nearly vanishes in the perpendicular Γ − X direction (i.e., in the a-direction) [24,25]. Even though this prediction is somewhat surprising, because no obvious pronounced anisotropy can be identified in the atomic structure of the material (see Figure 1a), indications of anisotropy (see Figure 1e) were indeed found when measuring the photoluminescence polar- ization dependence [24].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The FM ordering is remarkably retained in CrI 3 monolayer with the Curie temperature (T C ) ∼ 45 K and in Cr 2 Ge 2 Te 6 bilayer with T C ∼ 30 K under a tiny magnetic field. These discoveries stimulate extensive research on the emergent magnetism in the 2D limit and its promising technological applications in spintronics [3][4][5][6][7][8][9][10][11]. As the 2D isotropic Heisenberg spin systems have no long-range magnetic order at finite temperature according to the Mermin-Wagner theorem [12], magnetic anisotropy (MA) is indispensable for stabilizing the 2D magnetic order.…”
Section: Introductionmentioning
confidence: 99%